Carbon fiber reinforced nano-hydroxyapatite / polylactic acid composite material and preparation method thereof

By reinforcing carbon fibers in hydroxyapatite/polylactic acid composites, nano-hydroxyapatite/polylactic acid composites with significantly improved mechanical properties were prepared, which solved the problem of insufficient strength of existing materials when bearing loads, and achieved the effect of meeting the mechanical strength requirements of internal fixation materials in fractures.

CN119818738AInactive Publication Date: 2025-04-15西安蝾螈生物技术有限公司

Patent Information

Application Number
CN202510023515.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing hydroxyapatite materials have low flexural strength and poor toughness when subjected to loads, making them difficult to apply in bone tissues, and the nano-hydroxyapatite/synthetic polymer composites are not ideal in clinical practical applications.

Method used

The mechanical properties of the material are improved by mixing PLA, nHA and carbon fibers in a specific proportion and preparing through cast film formation, pre-impregnation belts and hot-pressing molding.

Benefits of technology

The mechanical properties of the composite material are significantly improved, the bending strength and flexural modulus are significantly improved, meeting the mechanical strength requirements of the fracture internal fixation material, and have good biocompatibility and absorbability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a carbon fiber reinforced nano-hydroxyapatite / polylactic acid composite material and a preparation method thereof. The preparation method comprises the following steps: 1, surface modification of hydroxyapatite (HA); 2, surface treatment of carbon fibers (CF); and 3, preparing the ternary composite material. DA (dopamine hydrochloride) is used for modifying hydroxyapatite nanoparticles, so that the dispersity of inorganic particles in a polymer matrix is improved; the strong oxidation effect of concentrated nitric acid increases the surface roughness of the carbon fibers, and improves the interface bonding strength among the components of the composite material. The ternary composite material obtained through compression molding has excellent mechanical properties. The CF-reinforced HA / PLA composite material not only can improve the mechanical properties of the composite material, but also can maintain the advantages of the HA / PLA composite material, and is expected to become a high-strength internal fracture fixation material with biological activity, absorbability and degradability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a carbon fiber reinforced nano-hydroxyapatite poly / lactic acid composite material and a preparation method thereof. Background Art

[0002] Hydroxyapatite (HA) has good biocompatibility and bioactivity as a medical ceramic material. Pure hydroxyapatite bioceramics are not only safe and non-toxic when implanted in the human body, but also can form strong chemical bonds with bone tissue at the interface, inducing and promoting bone tissue growth. However, pure hydroxyapatite artificial bone has low bending strength and poor toughness, and is not suitable as a load-bearing transplant material (currently, it is mainly used as a bone defect filler and a non-load-bearing implant in clinical practice), which limits its application in load-bearing parts. Compared with HA of normal particle size, HA nanoparticles have better physical and chemical properties. Such as higher solubility, greater surface activity, better biological activity, etc., it is a therapeutic material with better biocompatibility. Nano HA can generally be better dispersed in the PLA matrix and form better interface interactions with the matrix, so that the composite material has better mechanical properties.

[0003] Polylactic acid (PLA) is a new absorbable polymer with the characteristics of non-toxicity, non-irritation and good biocompatibility. It can be degraded into lactic acid in the human body and can be naturally metabolized without residue. It is widely used as fracture repair materials, surgical sutures, controlled-release drugs, etc. Although PLA has many excellent properties, the mechanical strength of the fracture internal fixation device made of pure PLA is low and cannot meet the fixation requirements of many functional bones. The acidic degradation products of PLA can be buffered by HA. At the same time, the osteoinductivity of HA can provide a good environment for bone cell adhesion and growth. The porous structure of the composite provides conditions for cell growth, tissue regeneration and vascularization, which meets the biological requirements of bone tissue engineering and is expected to become an ideal scaffold material in bone tissue engineering. Carbon fiber (CF) is an important branch of carbon materials with high strength, high modulus, high density and high temperature resistance. After being implanted in the human body, carbon fiber is non-carcinogenic, non-allergic, non-inflammatory and non-toxic, and has good hard tissue, soft tissue and blood compatibility. Reinforcing HA / PLA composites with CF can significantly improve the mechanical properties of the composites and meet the mechanical strength required as fracture internal fixation materials.

[0004] Bone defects caused by trauma, tumors, infection, surgery and other factors have always been a major problem faced by orthopedics, and have been the focus of research by orthopedic physicians and material researchers. Hydroxyapatite is widely used in bone tissue repair because of its structure similar to natural bone and good tissue compatibility. However, hydroxyapatite has poor mechanical properties, low bending strength, high brittleness, and easy fracture. Its elastic modulus and mechanical properties do not match those of human bones, making it difficult to use in bone tissue that bears loads. It can only be used for bone repair that does not bear loads or only bears small pure compressive stress loads.

[0005] In order to improve the strength and toughness of hydroxyapatite, the research of hydroxyapatite / natural polymer composite materials, hydroxyapatite / synthetic polymer composite materials, etc. has become a hot field, and its technology has also been rapidly developed, in the hope of synthesizing bone graft materials that can repair bone defects after implantation and ultimately achieve the same structure and mechanical properties as the host bone tissue. At present, researchers have synthesized a large number of nano-hydroxyapatite / natural polymer composite biomaterials, such as nano-hydroxyapatite / collagen fiber composite materials, nano-hydroxyapatite / chitosan composite materials, and nano-hydroxyapatite / polylactic acid composite materials, but most materials are not ideal in actual clinical applications. Because nano-hydroxyapatite / synthetic polymer composite materials are closer to natural bones in structure and have better mechanical properties, nano-hydroxyapatite / synthetic polymer composite materials have become the main research direction of bone tissue repair materials.

[0006] Existing reinforced PLA composites and HA / PLA composites have the disadvantages of being too acidic and easily causing inflammation in the body and having low mechanical strength. Carbon fiber (CF) reinforced hydroxyapatite polylactic acid composites, in which CF is oxidized by concentrated nitric acid, the surface roughness increases, and the interfacial bonding strength between the composite components is improved. Hydroxyapatite (HA) has good biocompatibility and bioactivity, and polylactic acid (PLA) can play a bonding role in the composite material. The obtained composite material has excellent mechanical properties, which is expected to improve the toughness of the material and meet the mechanical strength requirements of bone replacement implant materials. It is expected to become a high-strength fracture internal fixation material that is both bioactive and absorbable and degradable. Summary of the invention

[0007] The purpose of the present invention is to provide a fracture internal fixation material with good biocompatibility, bioactivity, good mechanical properties, absorbability and degradability, and the mechanical strength required for bone replacement implant materials.

[0008] To achieve the above object, the present invention provides a carbon fiber reinforced nano-hydroxyapatite / polylactic acid composite material, which is composed of 80% to 90% polylactic acid, 8.0% to 15% nano-hydroxyapatite and 2.0% to 5% carbon fiber in terms of mass percentage.

[0009] As a further improvement, the composite material consists of 85% polylactic acid, 12.5% ​​hydroxyapatite and 2.5% carbon fibers.

[0010] At the same time, the present invention provides a method for preparing a carbon fiber reinforced nano-hydroxyapatite / polylactic acid composite material, which is characterized by comprising:

[0011] S1, dissolving PLA in an organic solvent to prepare a 80% to 90% PLA viscous solution;

[0012] S2. Add nHA to the PLA viscous solution, and disperse the nHA particles evenly in the PLA viscous solution by stirring or ultrasonication to obtain a final mixed solution of 8.0% to 15% nHA.

[0013] S3, casting the carbon fiber with the final mixed solution to form a prepreg tape, removing the solvent to obtain an impregnated tape, wherein the mass percentage of the carbon fiber in the impregnated tape is 2.0% to 5%;

[0014] S4, placing the pre-impregnated tape into a mold, placing the mold with the pre-impregnated tape into a hot press, hot pressing for 10 to 20 minutes at 140°C to 160°C and 10 to 20 MPa, opening the mold and taking out the sample, thereby obtaining the composite material.

[0015] As a further improvement, the nHA is obtained by surface modification of nano-hydroxyapatite, comprising the following steps:

[0016] S21), dissolving the nano-hydroxyapatite in purified water by ultrasonic stirring in an ice bath to prepare a nano-hydroxyapatite suspension with a concentration of 10 to 50 mg / mL;

[0017] S22), adding a certain concentration of dopamine hydrochloride solution to the nano-hydroxyapatite suspension so that the final content of dopamine hydrochloride is 1-10%;

[0018] S23), the dopamine hydrochloride solution prepared in step S22) is then subjected to sufficient ultrasonic stirring, and then filtered, washed, and dried to obtain nHA.

[0019] As a further improvement, the carbon fiber is obtained by surface treatment, comprising the following steps:

[0020] S31), cleaning: putting the carbon fiber material into a Soxhlet extractor filled with acetone, extracting with acetone at a temperature of 60 to 100° C. to remove the sizing agent and impurities on the surface of the carbon fiber material, and drying the cleaned carbon fiber material in a blast drying oven at 60 to 80° C. to obtain a dry carbon fiber material;

[0021] S32), oxidation: the dried carbon fiber material is reflux-oxidized in concentrated nitric acid at 60-80°C for 5 hours, then washed with a large amount of purified water, and then dried in a blast drying oven at 60-100°C to obtain the carbon fiber.

[0022] As a further improvement, the organic solvent in S1 is chloroform or dichloromethane.

[0023] As a further improvement, in S31), the carbon fiber material is carbon fiber powder or chopped carbon fiber, or a mixture of the two.

[0024] As a further improvement, the fiber length of the carbon fiber powder is 30 to 300 um, and the fiber length of the chopped carbon fiber is 3 to 10 mm.

[0025] As a further improvement, the molar mass of PLA is 100-200 kg / mol.

[0026] The beneficial effects of the present invention are as follows: the CF-reinforced HA / PLA composite material can not only improve the mechanical properties of the composite material, but also maintain the advantages of the HA / PLA composite material, and is expected to become a high-strength fracture internal fixation material that is both bioactive and absorbable and degradable. DETAILED DESCRIPTION

[0027] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined purpose, the specific implementation methods, structural features and effects of the present invention are described in detail as follows in combination with the embodiments. In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail in combination with the embodiments. It should be pointed out that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. In order to provide a fracture internal fixation material with good biocompatibility, biological activity, good mechanical properties, absorbability and degradability that meets the mechanical strength of bone replacement implant materials, this embodiment provides a carbon fiber reinforced nano-hydroxyapatite / polylactic acid composite material, which is composed of 80% to 90% polylactic acid, 8.0% to 15% nano-hydroxyapatite and 2.0% to 5% carbon fiber in terms of mass percentage.

[0028] At the same time, a method for preparing a composite material of carbon fiber reinforced nano-hydroxyapatite / polylactic acid is also provided, comprising:

[0029] S1. Dissolving PLA in an organic solvent to prepare an 80% to 90% PLA viscous solution; wherein the molar mass of PLA is 100 to 200 kg / mol.

[0030] S2. Add nHA to the PLA viscous solution, and disperse the nHA particles evenly in the PLA viscous solution by stirring or ultrasonication to obtain a final mixed solution of 8.0% to 15% nHA.

[0031] S3, casting the carbon fiber with the final mixed solution to form a prepreg tape, removing the solvent to obtain an impregnated tape, wherein the mass percentage of the carbon fiber in the impregnated tape is 2.0% to 5%;

[0032] S4, placing the pre-impregnated tape into a mold, placing the mold with the pre-impregnated tape into a hot press, hot pressing for 10 to 20 minutes at 140°C to 160°C and 10 to 20 MPa, opening the mold and taking out the sample, thereby obtaining the composite material.

[0033] Wherein, nHA is obtained by surface modification of nano-hydroxyapatite, comprising the following steps:

[0034] S21), dissolving the nano-hydroxyapatite in purified water by ultrasonic stirring in an ice bath to prepare a nano-hydroxyapatite suspension with a concentration of 10 to 50 mg / mL;

[0035] S22), adding a certain concentration of dopamine hydrochloride solution to the nano-hydroxyapatite suspension to make the final dopamine hydrochloride content 1-10%; wherein the content of dopamine hydrochloride DA is preferably 2%, 4%, 5% or 6%, and the concentration of nHA is 8%.

[0036] S23), the dopamine hydrochloride solution prepared in step S22) is then subjected to sufficient ultrasonic stirring, and then filtered, washed, and dried to obtain nHA.

[0037] The carbon fiber is obtained by surface treatment, including the following steps:

[0038] S31), cleaning: putting the carbon fiber material into a Soxhlet extractor filled with acetone, extracting with acetone at a temperature of 60 to 100° C. to remove the sizing agent and impurities on the surface of the carbon fiber material, and drying the cleaned carbon fiber material in a blast drying oven at 60 to 80° C. to obtain a dry carbon fiber material;

[0039] S32), oxidation: the dried carbon fiber material is reflux-oxidized in concentrated nitric acid at 60-80°C for 5 hours, then washed with a large amount of purified water, and then dried in a blast drying oven at 60-100°C to obtain the carbon fiber.

[0040] Moreover, the organic solvent described in S1 is chloroform or dichloromethane. The carbon fiber (carbon fiber material, here it is necessary to determine whether it is a carbon fiber material before surface treatment or a carbon fiber obtained after surface treatment. If it is before treatment, it is defined as a carbon fiber material, and if it is after surface treatment, it is defined as carbon fiber) in S31 is one or a mixture of carbon fiber powder or chopped carbon fiber. The fiber length of the carbon fiber powder here is 30 to 300um, and the fiber length of the chopped carbon fiber is 3 to 10mm.

[0041] Now let's take an example to illustrate

[0042] Example 1

[0043] The components and their weight percentage contents of the carbon fiber reinforced nano-hydroxyapatite / polylactic acid composite material are as follows: polylactic acid (PLA) 90%, nano-hydroxyapatite (HA) 8.0%, and carbon fiber (CF) 2.0%.

[0044] Preparation method:

[0045] PLA is dissolved in an organic solvent (generally chloroform, dichloromethane or others) to prepare a viscous solution with a concentration of 90%.

[0046] Then nHA was added into the viscous solution, and nHA particles were evenly dispersed in the PLA solution by stirring or ultrasonication. The final concentration of nHA in the solution was 8%.

[0047] The carbon fiber is then cast with the mixed solution to form a pre-impregnated tape, and the solvent is removed by natural air drying and heating to obtain an impregnated tape, with a CF concentration of 2%.

[0048] The impregnated tape was placed in a mold, and the mold with the prepreg tape was placed in a hot press. The mold was hot-pressed at 140°C and 20 MPa for 10 minutes to form the sample, and the mold was opened to take out the sample.

[0049] Example 2

[0050] The components and their weight percentage contents of the carbon fiber reinforced nano-hydroxyapatite / polylactic acid composite material are as follows: polylactic acid (PLA) 85%, nano-hydroxyapatite (HA) 12.5%, and carbon fiber (CF) 2.5%.

[0051] Preparation method:

[0052] PLA is dissolved in an organic solvent (generally chloroform, dichloromethane or others) to prepare a viscous solution with a concentration of 85%.

[0053] Then nHA was added into the viscous solution, and nHA particles were evenly dispersed in the PLA solution by stirring or ultrasonication. The final concentration of nHA in the solution was 12.5%.

[0054] The carbon fiber is then cast with the mixed solution to form a pre-impregnated tape, and the solvent is removed by natural air drying and heating to obtain an impregnated tape, with a CF concentration of 2.5%.

[0055] The prepreg tape was placed in a mold, and the mold with the prepreg tape was placed in a hot press. The prepreg tape was hot pressed at 150°C and 15 MPa for 15 minutes to form the prepreg tape. The mold was opened and the sample was taken out.

[0056] Example 3

[0057] The components and weight percentage contents of the carbon fiber reinforced nano-hydroxyapatite / polylactic acid composite material are as follows: polylactic acid (PLA) 80%, nano-hydroxyapatite (HA) 15%, and carbon fiber (CF) 5%.

[0058] Preparation method:

[0059] 1) Dissolve PLA in an organic solvent (generally chloroform, dichloromethane or others) to prepare a viscous solution with a concentration of 80%.

[0060] 2) nHA is then added to the viscous solution, and the nHA particles are evenly dispersed in the PLA solution by stirring or ultrasonication. The final concentration of nHA in the solution is 15%.

[0061] 3) The carbon fiber is then cast with the above-mentioned mixed solution to form a pre-impregnated tape, and the solvent is removed by natural air drying and heating to obtain an impregnated tape, and the concentration of CF is 5%.

[0062] 4) Place the prepreg tape into a mold, place the mold with the prepreg tape into a hot press, hot press for 20 minutes at 160°C and 10 MPa, and open the mold to take out the sample.

[0063] The mechanical properties of carbon fiber reinforced nano-hydroxyapatite / polylactic acid composites are tested as shown in the following table:

[0064]

[0065] The composite material obtained by carbon fiber reinforced nano-hydroxyapatite / polylactic acid has excellent mechanical properties, with a flexural strength of about 4 to 7 times that of the HA / PLA composite material and a flexural modulus of about 3 to 5 times that of the HA / PLA composite material. The composite material has good mechanical strength retention and meets the mechanical strength required as a fracture internal fixation material.

Claims

1. A carbon fiber reinforced nano-hydroxyapatite / polylactic acid composite material, characterized in that: Calculated by mass percentage, it consists of 80% to 90% of polylactic acid, 8.0% to 15% of nano hydroxyapatite and 2.0% to 5% of carbon fiber.

2. The composite material according to claim 1, characterized in that According to mass fraction, the composite material consists of 85% of polylactic acid, 12.5% ​​of nano-hydroxyapatite and 2.5% of carbon fiber.

3. A method for preparing the carbon fiber reinforced nano-hydroxyapatite / polylactic acid composite material according to claim 1 or 2, characterized in that: include, S1, dissolving PLA in an organic solvent to prepare a 80% to 90% PLA viscous solution; S2. Add nHA to the PLA viscous solution, and disperse the nHA particles evenly in the PLA viscous solution by stirring or ultrasonication to obtain a final mixed solution of 8.0% to 15% nHA. S3, casting the carbon fiber with the final mixed solution to form a prepreg tape, removing the solvent to obtain an impregnated tape, wherein the mass percentage of the carbon fiber in the impregnated tape is 2.0% to 5%; S4, placing the pre-impregnated tape into a mold, placing the mold with the pre-impregnated tape into a hot press, hot pressing for 10 to 20 minutes at 140°C to 160°C and 10 to 20 MPa, opening the mold and taking out the sample, thereby obtaining the composite material.

4. The preparation method according to claim 3, characterized in that: The nHA is obtained by surface modification of nano-hydroxyapatite, comprising the following steps: S21), dissolving the nano-hydroxyapatite in purified water by ultrasonic stirring in an ice bath to prepare a nano-hydroxyapatite suspension with a concentration of 10 to 50 mg / mL; S22), adding a certain concentration of dopamine hydrochloride solution to the nano-hydroxyapatite suspension so that the final content of dopamine hydrochloride is 1-10%; S23), the dopamine hydrochloride solution prepared in step S22) is then subjected to sufficient ultrasonic stirring, and then filtered, washed, and dried to obtain nHA.

5. The preparation method according to claim 3, characterized in that: The carbon fiber is obtained by surface treatment, comprising the following steps: S31), cleaning: putting the carbon fiber material into a Soxhlet extractor filled with acetone, extracting with acetone at a temperature of 60 to 100° C. to remove the sizing agent and impurities on the surface of the carbon fiber material, and drying the cleaned carbon fiber material in a blast drying oven at 60 to 80° C. to obtain a dry carbon fiber material; S32), oxidation: the dried carbon fiber material is reflux-oxidized in concentrated nitric acid at 60-80°C for 5 hours, then washed with a large amount of purified water, and then dried in a blast drying oven at 60-100°C to obtain the carbon fiber.

6. The preparation method according to claim 3, characterized in that: The organic solvent in S1 is chloroform or dichloromethane.

7. The preparation method according to claim 5, characterized in that: In S31), the carbon fiber material is carbon fiber powder or chopped carbon fiber, or a mixture of the two.

8. The preparation method according to claim 7, characterized in that: The fiber length of the carbon fiber powder is 30 to 300 μm, and the fiber length of the chopped carbon fiber is 3 to 10 mm.

9. The preparation method according to claim 3 or 4 or 5 or 6 or 7 or 8, characterized in that: The molar mass of the PLA is 100-200 kg / mol.

Citation Information

Patent Citations

  • Method for preparing bone screw biological compound material

    CN101301495A

  • Aliphatic polyester-nano hydroxyapatite composite material and preparation method thereof

    CN105816918A

  • Composite biological material and preparing method

    CN1850300A

Cited By

  • Lithium battery solid electrolyte coating based on sodium amino sulfonated cellulose, preparation method and negative pole piece of lithium battery solid electrolyte coating

    CN121709701A